Determining the optimal tryptophan:lysine ratio for the segregated early-weaned pigs (25 to 50 lb) - J A Loughmiller; D A Knabe; K Hongtrakul; S Moser; C Civis; P R O'Quinn; J W Smith II; Jim L Nelssen; Michael D Tokach; Robert D Goodband (Kansas Agricultural Experiment Station Research Reports, 1997)
A 21 d growth trial was conducted to evaluate the effects of increasing the apparent digestible tryptophan:lysine ratio on growth performance of the 25 to 50 lb pig raised in a high-health, segregated early-weaning (SEW) system. Ten diets were fed with two levels of lysine (.75% and 1.10% apparent digestible lysine) and five apparent digestible tryptophan levels (13, 16, 19, 22, or 25% of lysine). Feeding the high dietary lysine consistently improved ADG and FIG and reduced ADFI. Increasing the tryptophan: lysine ratio did not improve overall performance. Based upon our results, the dietary tryptophan level to maximize growth performance in the 25 to 50 lb pig is not greater than 13% of apparent digestible lysine.; Swine Day, Manhattan, KS, November 20, 1997
Keywords: Swine day; 1997; Kansas Agricultural Experiment Station contribution; no. 98-142-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 795; Swine; Tryptophan; Lysine; SEW pig